Alternative scale-invariant Higgs mass generation using hidden sector SU(Nc)xU(1)3. (April 2020) - Soesanto, Q M B; Azam, M; Richardina, V; Satriawan, M
Abstract: Spontaneous Symmetry Breaking (SSB) is a method to generate mass for all elementary particles in the Standard Model (SM). Even so, it turns out that the Higgs mass term in the Higgs potential, which responsible for the SSB, does not scale invariant. Based on this problem, instead of using SSB from the SM to explain the origin of mass, we erase Higgs's mass term from the SM Lagrangean and introduce a hidden sector Lagrangean to produce an alternative way to generate Higgs mass. We use Scalar Bilinear Condensate ineffective theory to obtain Higgs mass via the Higgs portal and generate the SSB. The hidden sector in this alternative model is described by an SU ( N C A ) gauge theory with U (1) 3 flavor. In the calculation, we use the Mean-Field Approximation Lagrangean in obtaining the vacuum of the potential to get a Higgs mass term in this model.